Um estudo introdutório da literatura de João Carlos Marinho - Martins, Ana Suellen [UNESP] (2013)
João Carlos Marinho (1935-) is one of the greats of children's literature in Brazil, still in activity. Although his writing is legitimized by various scholars in the field, there is no overview study of his works aimed at children. Searching with this work, so make an introductory study of the production infantile-juvenile writer highlighting the series created by Marinho, the Fat‟s Gang, which includes twelve narratives: O gênio do crime (1969 ), O caneco de prata (1971), Sangue fresco (1982 ), O livro da Berenice (1984 ), Berenice detetive (1987), Berenice contra o maníaco janeloso (1990), Cascata de cuspe (1992), Conde Futreson (1994), O Disco ( 1996), A catástrofe do Planeta Ebulidor (1998), O gordo contra os pedófilos (2001) and Assassinato na literatura infantil (2005). Objective of the work is also making a rescue of critical fortune of the author's work, as well as compiling interviews given by Marinho in various mediums. Were collated the various editions released by the author in order to identify the changes in graph - editorial projects of each book and also changes in the content of the plot . To understand the production of the literary scene brazilian of Marinho, specifically the infantile-juvenile while renewal process text for children and youth were used studies of Regina Zilberman, Marisa Lajolo, Nelly Novaes Coelho, Edmir Perrotti, among other researchers. It could be observed that Marinho, in his work, learned to value the historical context in which it appears the narrative action, revealing their perception of social reality, but in the background without leaving the specificity of literature, emphasizing the aesthetic character of the literary work